2021
DOI: 10.1002/etc.5191
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Fate and Partitioning Behavior of Antibiotics in the Aquatic Environment—A Review

Abstract: Antibiotics (ABs) in the aquatic environment is a major problem due to the emergence of antibiotic resistance. The long-term ecological impact on the aquatic environment is unknown. Many sources allow entry of ABs into the environment, including Wastewater Treatment Plants (WWTPs), agricultural run-off, hospital effluent and landfill leachate. Concentrations of ABs in the aquatic environment vary significantly, studies have shown fluoroquinolones, tetracycline, macrolides, sulphonamides and penicillins to rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 148 publications
0
29
0
Order By: Relevance
“…However, a key factor is the "dilution effect", which in turn depends on river discharge and seasonal rainfall [65] and is particularly significant when WWTP effluents enter natural river water. Moreover, abiotic (e.g., photodegradation) and biotic degradation times and sorption onto particles can also determine contaminant concentrations [5,24]. In this study, emerging contaminants, and in particular pharmaceuticals, were found in higher amounts than PAHs, and this can be ascribed to the different chemical-physical properties of these molecules and different emission sources.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, a key factor is the "dilution effect", which in turn depends on river discharge and seasonal rainfall [65] and is particularly significant when WWTP effluents enter natural river water. Moreover, abiotic (e.g., photodegradation) and biotic degradation times and sorption onto particles can also determine contaminant concentrations [5,24]. In this study, emerging contaminants, and in particular pharmaceuticals, were found in higher amounts than PAHs, and this can be ascribed to the different chemical-physical properties of these molecules and different emission sources.…”
Section: Discussionmentioning
confidence: 70%
“…Antibiotics are emerging contaminants commonly found as river micro-pollutants [23,24] downstream from wastewater treatment plant outlets. Owing to their antimicrobial activity, they can kill or inhibit natural microbial populations involved in specific ecosystem functions (e.g., denitrification) [25] and, at the same time, they can select antibiotic resistant bacteria (ARB) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, large amounts of unused TC antibiotics will inevitably be released into the environment due to incomplete metabolism in humans, sewage effluents released from healthcare units, 1 and/or disposal of wastewater from the pharmaceutical factory, 2 resulting in increasing concern about their potential negative effects on the environment and public health. 3 Recently published studies have shown that antibiotics could cause toxic effects on micro-organisms, animals, and humans. 4,5 Note that antibiotics can potentially enter the groundwater environment through infiltration, runoff, and leaching, causing groundwater contamination and water quality reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics enter wastewater treatment plants in various forms as persistent substances due to their low metabolic rate and low biodegradation [3,4]. The presence and concentration enrichment of tetracycline in the aquatic environment can cause the enhancement and spread of tetracycline-resistant bacteria and resistance genes, even posing a potential risk to the ecosystem and human health [5][6][7]. The advanced treatment techniques include adsorption, flocculation, advanced oxidation technology, chemical degradation, and biological treatment [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%